(Mus musculus L.) على الدليل التطفيري لاناث الفئران المختبريه Neotigason دراسة تاثير عقار - ثاقب هبه (University of Thi-Qar Journal of Science, 2012)
The current research was designed to investigate the effect of intraperitonial (i.p.) injection of (10 mg/kg/day) and (20 mg/kg/day) of Neotigason drug in female laboratory mice Mus musculus. The experiment was carried out for 9 days of injection from the 5 th day – the 14 th day of pregnancy. Neotigason drug caused a significant increase in the number of dead embryo or absorbed embryo in the female mice uterine with the control group. The present study also revealed that there is no significant differences between high and low doses.